Prevalence and characterizations of current smoking habit of Iranian medical university students: A cross-sectional study in mental health - Seghatoleslam, T.; Agin, K.; Zahiroddin, A.; Habil, H.; Ardakani, A.; West, R.; Seghatoleslam, N. (2013)
Background: This cross sectional study was carried out on medical university students of Iran. Materials and Methods: A total of 500 participants from a total of 1866 followed the criteria of the study. The mean age was 24.6 Â± 3.3 SD, males 70 and females 30. Results: The prevalence of smokers was 27, and their initiation into smoking had occurred under 18 years of age (89.6). The result shows that, males were more likely to smoke than females. The data on unemployment, marriage, residency in Tehran, no resident dormitory and a wealthy background had meaningful frequency. In addition, data on family conflicts and separation were low in frequency. Ages 20-25 had a high frequency (56.6). The consumption of up to 20 cigarettes per day was found highest in the 20-25 class at a rate of 32.6, which is quite alarming. Motivations for taking up smoking were curiosity friends' interest and family, and were insignificant as habit, hobby and depression. Shisha was used (72.2) more than other nicotine delivery packages. Conclusion: A noticeable prevalence current smoking habits was observed among medical students. Therefore, universities should issue nonsmoking regulations and awareness program among students which will significantly affect the national health. Â© 2013 Japan International Cultural Exchange Foundation and Japan Health Sciences University.